76.25.15 problem 19
Internal
problem
ID
[17828]
Book
:
Differential
equations.
An
introduction
to
modern
methods
and
applications.
James
Brannan,
William
E.
Boyce.
Third
edition.
Wiley
2015
Section
:
Chapter
6.
Systems
of
First
Order
Linear
Equations.
Section
6.3
(Homogeneous
Linear
Systems
with
Constant
Coefficients).
Problems
at
page
408
Problem
number
:
19
Date
solved
:
Tuesday, January 28, 2025 at 11:03:31 AM
CAS
classification
:
system_of_ODEs
\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=2 x_{1} \left (t \right )+2 x_{2} \left (t \right )-x_{4} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=2 x_{1} \left (t \right )-x_{2} \left (t \right )+2 x_{4} \left (t \right )\\ \frac {d}{d t}x_{3} \left (t \right )&=3 x_{3} \left (t \right )\\ \frac {d}{d t}x_{4} \left (t \right )&=-x_{1} \left (t \right )+2 x_{2} \left (t \right )+2 x_{4} \left (t \right ) \end{align*}
✓ Solution by Maple
Time used: 0.151 (sec). Leaf size: 74
dsolve([diff(x__1(t),t)=2*x__1(t)+2*x__2(t)-0*x__3(t)-1*x__4(t),diff(x__2(t),t)=2*x__1(t)-1*x__2(t)+0*x__3(t)+2*x__4(t),diff(x__3(t),t)=0*x__1(t)-0*x__2(t)+3*x__3(t)+0*x__4(t),diff(x__4(t),t)=-1*x__1(t)+2*x__2(t)+0*x__3(t)+2*x__4(t)],singsol=all)
\begin{align*}
x_{1} \left (t \right ) &= {\mathrm e}^{-3 t} c_{2} +c_{3} {\mathrm e}^{3 t} \\
x_{2} \left (t \right ) &= -2 \,{\mathrm e}^{-3 t} c_{2} -2 c_{3} {\mathrm e}^{3 t}+c_{1} {\mathrm e}^{3 t} \\
x_{3} \left (t \right ) &= c_4 \,{\mathrm e}^{3 t} \\
x_{4} \left (t \right ) &= {\mathrm e}^{-3 t} c_{2} -5 c_{3} {\mathrm e}^{3 t}+2 c_{1} {\mathrm e}^{3 t} \\
\end{align*}
✓ Solution by Mathematica
Time used: 0.025 (sec). Leaf size: 282
DSolve[{D[x1[t],t]==2*x1[t]+2*x2[t]-0*x3[t]-1*x4[t],D[x2[t],t]==2*x1[t]-1*x2[t]+0*x3[t]+2*x4[t],D[x3[t],t]==0*x1[t]-0*x2[t]+3*x3[t]+0*x4[t],D[x4[t],t]==-1*x1[t]+2*x2[t]+0*x3[t]+2*x4[t]},{x1[t],x2[t],x3[t],x4[t]},t,IncludeSingularSolutions -> True]
\begin{align*}
\text {x1}(t)\to \frac {1}{6} e^{-3 t} \left (c_1 \left (5 e^{6 t}+1\right )+(2 c_2-c_3) \left (e^{6 t}-1\right )\right ) \\
\text {x2}(t)\to \frac {1}{3} e^{-3 t} \left (c_1 \left (e^{6 t}-1\right )+c_2 \left (e^{6 t}+2\right )+c_3 \left (e^{6 t}-1\right )\right ) \\
\text {x4}(t)\to \frac {1}{6} e^{-3 t} \left (-\left (c_1 \left (e^{6 t}-1\right )\right )+2 c_2 \left (e^{6 t}-1\right )+c_3 \left (5 e^{6 t}+1\right )\right ) \\
\text {x3}(t)\to c_4 e^{3 t} \\
\text {x1}(t)\to \frac {1}{6} e^{-3 t} \left (c_1 \left (5 e^{6 t}+1\right )+(2 c_2-c_3) \left (e^{6 t}-1\right )\right ) \\
\text {x2}(t)\to \frac {1}{3} e^{-3 t} \left (c_1 \left (e^{6 t}-1\right )+c_2 \left (e^{6 t}+2\right )+c_3 \left (e^{6 t}-1\right )\right ) \\
\text {x4}(t)\to \frac {1}{6} e^{-3 t} \left (-\left (c_1 \left (e^{6 t}-1\right )\right )+2 c_2 \left (e^{6 t}-1\right )+c_3 \left (5 e^{6 t}+1\right )\right ) \\
\text {x3}(t)\to 0 \\
\end{align*}